Physical image quality evaluation of medical radiographs - Wan Hassan, Wan Muhamad Saridan; Munajat, Yusof; Sahibuddin, Shamsul (Malaysian Institute of Physics, 2002)
The noise equivalent quanta (NEQ) has been recommended as a measure of physical quality of medical images. Digitised data of medical radiographs in a previous work have been analysed in terms of resolution via the modulation transfer function (MTF) and noise via the noise power spectrum (NPS), but not in terms of NEQ. As the NEQ is currently regarded as a basic device performance measure of the imaging system, it is very useful to be able to determine it. The average gamma of the radiograph was computed, both the MTF and the NPS data were interpolated and these values were used to compute the NEQ. The computation shows that for spatial frequency range 0–0.7 cycles/mm the NEQ of Lanex Regular/T Mat G screen-film combination is slightly lower than that of Lanex Regular/T Mat L, for 0.7–1.5 cycles/mm the NEQ of both are almost the same, and for frequencies greater than 1.5 cycles/mm the NEQ of the former is greater than that of the latter.